Factual investigation about the short-term weight loss of the male university judo players. - Fujimoto, T.; Sonobe, Y.; Kojima, A.; Tanabe, M.; Yamamoto, Y.; Kusumoto, Y. (Association for the Scientific Studies on Judo, Kodokan, 2015)
The purpose of this investigation was to examine the incidence of weight loss and the psychological and physical effects of short-term weight loss on male university judo athletes. The participants were 276 male university judo athletes. We developed a questionnaire to investigate issues surrounding weight loss. Chi-square tests and one- and two-sample t-tests were conducted to analyze the results. Approximately one-half of the respondents had experienced weight loss, and athletes with lighter classes experienced greater than heavier classes. For many of the athletes, the weight loss was short-term. In addition, a few players had experience of learning weight loss methods, and many athletes underwent weight loss as early as junior high school or during the period of growth in high school. Approximately 80% of the players who lost weight reported negative psychological and physical consequences. Furthermore, negative psychological responses were significantly higher than negative physical responses. Therefore, psychotherapeutic interventions, such as autogenic training, are necessary to support those judo athletes who undergo short-term weight loss. In relation to long-term weight loss, it is clear that a leader with specialized knowledge in nutrition is necessary to educate and instruct these athletes about weight loss for their psychological and physical well-being.